2016
DOI: 10.3390/nu8100631
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25-Hydroxyvitamin D Is Related to Protein Signaling Involved in Glucose Homeostasis in a Tissue-Specific Manner

Abstract: Vitamin D has been suggested to play a role in glucose metabolism. However, previous findings are contradictory and mechanistic pathways remain unclear. We examined the relationship between plasma 25-hydroxyvitamin D (25(OH)D), insulin sensitivity, and insulin signaling in skeletal muscle and adipose tissue. Seventeen healthy adults (Body mass index: 26 ± 4; Age: 30 ± 12 years) underwent a hyperinsulinemic-euglycemic clamp, and resting skeletal muscle and adipose tissue biopsies. In this cohort, the plasma 25(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Vitamin D influences the vaginal microbiome by maintaining and strengthening the vaginal epithelium, by inducing expression of LL-37, an antimicrobial peptide, and most importantly, by inducing the insulin synthesis and inactivating the glycogen synthase kinase, that subsequently, stimulates the glycogen synthesis. This glycogen acts as a substrate for Lactobacilli and helps in lowering pH by production of lactic acid and therefore, vitamin D deficiency in a pregnant female can lead to spontaneous PTL ( 85 87 ).…”
Section: Role Of Microbiota In Adverse Pregnancy Outcomementioning
confidence: 99%
“…Vitamin D influences the vaginal microbiome by maintaining and strengthening the vaginal epithelium, by inducing expression of LL-37, an antimicrobial peptide, and most importantly, by inducing the insulin synthesis and inactivating the glycogen synthase kinase, that subsequently, stimulates the glycogen synthesis. This glycogen acts as a substrate for Lactobacilli and helps in lowering pH by production of lactic acid and therefore, vitamin D deficiency in a pregnant female can lead to spontaneous PTL ( 85 87 ).…”
Section: Role Of Microbiota In Adverse Pregnancy Outcomementioning
confidence: 99%
“…In close agreement with our findings, studies in adipocytes found that half-maximal Akt1 cellular signaling activity is achieved when the kinase is 5–22% phosphorylated [ 13 ]. In studies of human tumors [ 12 , 13 , 14 , 15 ] and in clinical diagnostic settings [ 14 , 15 ], the phosphorylation status of Akt1 at Ser473 only is often used as a marker or proxy for Akt1 activity. Our work [ 12 ] and work by others [ 16 ] found that phosphorylation of Thr308 alone was sufficient for maximal Akt1 signal prorogation in cells.…”
Section: Introductionmentioning
confidence: 99%
“…Under experimental conditions, vitamin D has been shown to significantly inhibit the hepatic expression of pro-fibrotic mediators such as platelet-derived growth factor (PDGF) and transforming growth factor β (TGF-β) [ 7 , 9 ] and to suppress the expression of collagen, α-smooth muscle actin and tissue inhibitors of metalloproteinase-1; however, its protective action against fibrosis was ineffective once overt hepatic cirrhosis was established [ 9 ]. Furthermore, vitamin D has been proposed as an effective modulator of insulin sensitivity in several experimental models [ 11 , 12 , 13 ] and epidemiological data show the existence of a tight correlation between low circulating vitamin D levels and the presence of obesity [ 14 ], T2D [ 15 ] and insulin resistance-related conditions [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%